2014
DOI: 10.1016/j.jpubeco.2014.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Work and tax evasion incentive effects of social insurance programs

Abstract: This article studies how social insurance programs shape individual's incentives to take up registered employment and to report earnings to the tax authorities. The analysis is based on a social insurance reform in Uruguay that extended healthcare coverage to the dependent children of registered private-sector workers. The identification strategy relies on a comparison between individuals with and without dependent children before and after the reform. The reform increased benefit-eligible registered employmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
26
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 47 publications
6
26
0
2
Order By: Relevance
“…Figure 19 reports that the implied ETI for workers in a single firm is about 0.134 while for workers in multiple firms is substantially low (0.06). This evidence is consistent with previous studies that have shown the reported taxable income response to tax incentives is stronger in contexts with lower cost of coordination for employers and employees, like in smaller firms (Bergolo and Cruces 2014;Best 2015).…”
Section: So No Responses In Gross Labor Income At All?supporting
confidence: 93%
See 2 more Smart Citations
“…Figure 19 reports that the implied ETI for workers in a single firm is about 0.134 while for workers in multiple firms is substantially low (0.06). This evidence is consistent with previous studies that have shown the reported taxable income response to tax incentives is stronger in contexts with lower cost of coordination for employers and employees, like in smaller firms (Bergolo and Cruces 2014;Best 2015).…”
Section: So No Responses In Gross Labor Income At All?supporting
confidence: 93%
“…We present direct evidence of gross income unilateral misreporting by the wage earners, but most importantly we document how tax evasion behavior react to local tax incentives by showing a sharp increase in underreporting just at the kink point. In line with some previous studies (Bergolo and Cruces 2014;Best 2015), we also document evidence consistent with the hypothesis of collusion between employee and employer to undereport earnings in a context of low coordination costs . These results indicate the limits of third-party based enforcement in developing countries, and highlight the importance of improving the enforcement capacity of tax authorities.…”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…Francesconi et al, 2009;Eissa & Hoynes, 2004) and developing (e.g. Bérgolo & Cruces, 2014) countries.…”
mentioning
confidence: 99%
“…While the impact of the informality effects on tax collection can be informative (see for instance Bergolo and Cruces, 2014), measurement of the relevant elasticities is crucial for a full welfare analysis that quantifies the efficiency 3While AFAM's design implies a potential effect on the intensive margin of labor supply, we concentrate on the extensive margin of response. Unlike Kleven and Waseem (2013) or Kline and Tartari (2016), we are unable to measure (local) labor supply effects at the intensive margin since our data does not cover hours worked nor earnings (see Section 4).…”
Section: Introductionmentioning
confidence: 99%